Arsenic mitigation measures in Bangladesh - Zaved Kaiser Khan, Mohammad (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2012)
The scale of arsenic toxicity of the groundwater in Bangladesh is greater than any environmental debacle in the history of human civilization. The main route of arsenic accumulation in the human body is the ingestion of arsenic tainted water. Because of the undetectable nature of arsenic poisoning at the early stage and lack of awareness due to mass illiteracy, poverty and malnutrition, arsenic related ailments may cause death. However, this paper mainly discusses arsenic mitigation measures in Bangladesh. Although a piped surface water supply after treatment is the absolute solution to get rid of this crisis, the weak economic background of Bangladesh does not support supplying such water to every corner of rural areas. Hence research groups have developed their own methods to suit the local environment, using locally available materials and approaches based on the common method of arsenic removal: use of oxidizing agents, followed by flocculation and precipitation. Again, among different alternative water supply options, deep tubewells, which have been used by the communities in Bangladesh during the past few decades, appear to be a more suitable alternate option. Moreover, household-based arsenic filters can be a good choice if proper maintenance can be done.